2020
DOI: 10.13057/biodiv/d211051
|View full text |Cite
|
Sign up to set email alerts
|

The tolerance of oil palm (Elaeis guineensis) seedlings to Al stress is enhanced by citric acid and natural peat water

Abstract: Abstract. Hidayah AN, Yahya S, Sopandie D. 2020. The tolerance of oil palm (Elaeis guineensis) seedlings to Al stress is enhanced by citric acid and natural peat water. Biodiversitas 21: 4850-4858. Management technology on soil containing high levels of Aluminum (Al) toxicity is still needed to be developed so that the growth and development of plants will be optimum. The aims of the research were to investigate the response of oil palm seedlings (Elaeis guineensis Jacq.) toward aluminum stress, and to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Besides a citric acid, [12] mentioned that salicylic acid also plays a role in stimulating antioxidants so that lipid peroxidase was slowed down. This was in agreement with our work on oil palm seedlings exposed to Al stress under nutrient culture [24]. 3 revealed a decrease in the number of rejected bunches due to the applications of exogenous compounds in all treatments compared to controls, the decrease of which was followed by an increase in the average bunches weight (Table 3).…”
Section: Photosynthesis Ratesupporting
confidence: 92%
See 1 more Smart Citation
“…Besides a citric acid, [12] mentioned that salicylic acid also plays a role in stimulating antioxidants so that lipid peroxidase was slowed down. This was in agreement with our work on oil palm seedlings exposed to Al stress under nutrient culture [24]. 3 revealed a decrease in the number of rejected bunches due to the applications of exogenous compounds in all treatments compared to controls, the decrease of which was followed by an increase in the average bunches weight (Table 3).…”
Section: Photosynthesis Ratesupporting
confidence: 92%
“…Based on these results, it is clearly seen that salicylic acid and citric acid exert a significant positive influence on the increase in the rate of photosynthesis. According to [22][23][24] the application of citric acid was able to increase the rate of photosynthesis on Al-stressed plants. Salicylic acid plays an important role in maintaining the integrity and function of photosystems in photosynthesis, which promoted plant tolerance to Al stress [25].…”
Section: Photosynthesis Ratementioning
confidence: 99%
“…Kpomblekou and Tabatabai [60] reported that the release of P from the PRs to acids was afected by the chemical structure, type, and position of the functional groups of the ligands and the concentration of the acids. Citric acid up to 100 ppm concentration increases the tolerance of oil palm seedlings to the stress of Al, becoming complex compounds that are difcult to dissolve [61]. In this research, 100−200 ppm was a concentration of OA that could provide lower soil exchangeable Al compared with other OA concentrations.…”
Section: Discussionmentioning
confidence: 73%
“…The characteristics of ultisol soils in oil palm plantation areas in Bengkulu are low pH (4,20), low C-organic, and very low nutrient content of N, P, and K-dd (Nurmegawati et al, 2020). Acidic soils such as ultisols have high mineral content, and Al inhibits root growth and decreases photosynthesis (Hidayah et al, 2020).…”
Section: Article Historymentioning
confidence: 99%